Occurrence, cultivar reaction and yield losses due to leaf blight of wheat - and RAJENDER SINGH, S.S. KARWASRA, M.S. BENIWAL (Indian Phytopathology, 2002)
During 1995-96 and 1996-97, 50 and 65 wheat samples affected by blight (caused by Helminthosporium sativum [Cochliobolus sativus] and Alternaria triticina) were collected from various locations in Haryana, India. Infection caused significant grain yield losses. The susceptibility of 16 wheat cultivars to C. sativus was assessed and only 2 (WH 157 and WH 283) were moderately resistant.